INCREASING PUBLIC KNOWLEDGE ABOUT STUNTING PREVENTION IN KALIJAGA VILLAGE - Ria Yulianti Triwahyuningsih; Lairie Lairie; Syahlini Gita Fitri; Syarifah Nur Intan; Tia Yulianti; Rizki Amalia; Vianty Mutya Sari; Rahma Amalia Sudrajat; Rinda Tri Wahyuni; Syafira Fatia; Siti Laela Sari Ningsih (Ann Publisher, 2026)
Background. Stunting is a serious health problem in RW 04 Kalijaga Village due to limited public knowledge of nutrition and child-rearing practices. Previous research has shown that education on innovative products made from tempeh waste has increased public knowledge of stunting prevention. Aims. This research aims to expand educational interventions by using animated videos as counseling media in Posyandu. Methods. The method used is quasi-experimental with a pre-post test design, as well as measuring public perception using the Likert scale. Result. The results showed an increase in knowledge from 70% to 95% and an 85% increase in positive perceptions. Implementation. The use of animated videos not only increases public understanding but also strengthens the results of previous research on the importance of visual-based education and innovative products in supporting stunting prevention.